2021
DOI: 10.1038/s41598-020-78533-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, modification and characterisation of cellulose from wild Dioscorea bulbifera

Abstract: This study attempted to valorise wild Dioscorea bulbifera yam presently known to be poisonous and inedible obtained from three sources. The functional properties as well as its chemical composition were determined and isolated. Isolated cellulose was modified by the actions of sodium hydroxide and maleic anhydride. The biomass, isolated products and modified cellulose were characterized. Results showed that the highest cellulose obtained was 82.6%. FT-IR results showed successful modification of cellulose with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…Similarly, a weak peak at 1470 cm −1 may be due to −CH 2 bending vibration. The strong peak at 1725 cm −1 was due to carbonyl (C=O) adsorption [15] . In this study, these peak values were observed as 1471 and 1725 cm −1 , respectively.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Similarly, a weak peak at 1470 cm −1 may be due to −CH 2 bending vibration. The strong peak at 1725 cm −1 was due to carbonyl (C=O) adsorption [15] . In this study, these peak values were observed as 1471 and 1725 cm −1 , respectively.…”
Section: Resultssupporting
confidence: 51%
“…The strong peak at 1725 cm À 1 was due to carbonyl (C=O) adsorption. [15] In this study, these peak values were observed as 1471 and 1725 cm À 1 , respectively. It was stated that the FT-IR spectrum of DOX exhibited multiple peaks at 3346, 2940, 2354 and 1072 cm À 1 , which corresponded to the different quinine and ketone carbonyls in DOX.…”
Section: Ft-ir Analysis Of Dox Pcec Pm and Dox-pmssupporting
confidence: 54%
“…X-ray diffraction measurements were made using the X’Pert PRO system, applying nickel filtered CuKα radiation (wavelength 1.54056 Å) in the 2θ angle range from 2° to 40°. The degree of crystallinity (X c , %) was calculated as the ratio of the surface area of signals corresponding to the crystalline phase to the total surface area under the XRD pattern [ 40 , 41 ]: where A cr is the surface area under crystalline peaks, and A am is the area of amorphous halo.…”
Section: Methodsmentioning
confidence: 99%
“…Both ethanol and cyclohexane are greener solvents compared to benzene which is carcinogenic. A previous study showed that extractive yield by ethanol-cyclohexane mixture is close to that obtained when ethanol-benzene mixture is used [ 25 ]. Initial attempt showed that the two solvents (ethanol-cyclohexane mixture and ethanol) gave the same yield of 4.2% extractives.…”
Section: Resultsmentioning
confidence: 72%
“…Recent efforts geared towards obtaining cellulose focus on abundant agricultural wastes in the environment. Isolation of cellulose and CNC from the following agricultural wastes has been reported: rice straw [ 20 ], coconut shell [ 16 ], ground nut shell [ 21 ], walnut shell [ 22 ], jackfruit peel [ 23 ], corn straw [ 24 ], aerial yam [ 25 ], bamboo [ 26 ] and sisal [ 27 ].…”
Section: Introductionmentioning
confidence: 99%